CLINICAL CASE OF ALIMENTARY OBESITY IN A DOG - Lokes-Krupka, T. (Scientific Progress & Innovations, 2019)
The aim of the article is to determine and analyze clinical, functional, and structural indices of domestic dog of pug breed for alimentary obesity. According to current researches of medical and veterinary scientists and practitioners, primary obesity (alimentary) is usually caused by excessive consuming easily digestible products (feeds) as a result of slow-moving. Morphometric calculations and score assessment of fleshing are recommended to be used to establish the fact of obesity. Biochemical and ultrasonographic studies should be performed to determine the functional changes in the internal organs and identify possible risks. The diagnostics of alimentary obesity in domestic dogs is based on the study of the disease clinical signs with subsequent ultrasonographic examination of the liver, determining the status of protein, bilirubin and lipid. We have found out that in case of the pathology the content of β-lipoproteins, cholesterols and common proteins increases. We have investigated and described the clinical case of alimentary obesity in a domestic seven- year-old dog of pug breed weighing 14.4 kg, which was excessive for the specified breed. The percentage of fat tissue in the body was 26.0 %. The established basic etiological factor was constantly available feed in the feeder, which contributed to its uncontrolled and excessive consumption by the animal. The main clinical manifestations of alimentary obesity in the domestic dog were: excessive body weight, drowsiness and easy tiredness, lack of breath, and lameness. The pathological process of the hepatobiliary system (increasing the activity of aminotransferase in the blood serum as compared with the physiological standard for such kinds of animals) and joint damage have been the result of excessive feeding. If the etiological factor is not influenced, the metabolic syndrome may develop in the animal in future. The obtained research data can be used by practicing doctors of veterinary medicine, as well as in educational activities − to promote rational and dosed feeding of animals.